Multiple Myeloma Outpatient Transplant Program in the Era of Novel Agents: State-of-the-Art - Martino, Massimo; Paviglianiti, Annalisa; Memoli, Mara; Martinelli, Giovanni; Cerchione, Claudio (Frontiers in Oncology, 2020)
Multiple myeloma (MM) is the most common indication for autologous stem cell transplantation (ASCT), and outpatient models have been widely developed in this setting. Although numerous studies have demonstrated the safety and feasibility of outpatient ASCT, it is not a routine procedure. Stringent guidelines for patient selection and clinical management, including functional status, caregiver support, and psychological aspects, are essential to identify eligible patients. However, there is still no general agreement on these criteria. Quality of life data are limited and contradictory. There is considerable variability in outpatient transplant models, and there are no randomised studies supporting the use of one over the other. Studies evaluating results in terms of long-term survival, transplant toxicity in comparison with a standard approach are lacking. The procedure is cost-effective within the context of a hospital budget, but an in-depth analysis of the real cost of these programmes has yet to be performed.